ミズホ コウゲン ノ ヒセツ ノ サンソ ドウイタイ ソセイ ト エンガン テイキアツ ニヨル スイジョウキ ユソウ ダイ1カイ ナンキョク キスイケン シンポジウム - 加藤, 喜久雄; カトウ, キクオ; 渡辺, 興亜; ワタナベ, オキツグ; 佐藤, 和秀; サトウ, カズヒデ; KATO, Kikuo; WATANABE, Okitsugu; SATOW, Kazuhide (1979)
P(論文) みすぼ高原の飛雪の酸素同位体組成(δ^<18>O)を求め,それを決定している因子を考察することにより,南極水床への水蒸気輸送に重荷な役割を果していると考えられる沿岸低気圧による水蒸気輸送について検討した.高度1800～2000m以下の地域の飛雪のδ^<18>0値には,気象の日変化が反映されており,その変動は沿岸低気圧による^<18>0に富んだ水蒸気の供給とよく相関している.高度のより大きい地域の飛雪のδ^<18>0値には,沿岸低気圧による^<18>0に富んだ水蒸気の供給の影響は見られない.これらのことは,高度1800～2000m以下の地域へは沿岸低気圧により^<18>Oに富んだ水蒸気が大量に供給されていることを示す.内陸にわずかに入るだけだ飛雪のみδ^<18>O値に著しい増大が見いだされた高度3100～3200mの地域は,沿岸低気圧と南極高気圧の勢力圏の境に当たる.この境は季節により変化していて,冬のみずほ基地(高度2230m)は南極高気圧下にあることが多いと考えられる. Oxygen isotopic composition of drifting snow sampled at the various stations along the traverse routes in Mlzuho Plateau was determined, in order to investigate transportation of water vapor to Antarctic ice sheet resulting from the approach of a circumpolar cvclone. The oxygen isotopic composition of drifting snow in every season at the stations below 1800 m in altitude is largely controlled by the supply of <18>^O-rich water vapor resulting from the approach of a circumpolar cyclone, but it is not so at the stations above 2000 m. A large anomaly is found in the variation with altitude of oxygen isotopic comnosition of drifting snow at the stations at altitudes between 3100 and 3200 m, in (austral) spring. The area where the anomaly is found is the boundary between the spheres of influence of circumpolar cyclones and Antarctic anticyclones, and it changes its position seasonally. In winter, Mlzuho Station (2230 m in altitude) is considered to be hardly influenced by circumpolar cyclones. departmental bulletin paper